1987
DOI: 10.1210/jcem-65-6-1192
|View full text |Cite
|
Sign up to set email alerts
|

Functional Differentiation in Steroidogenesis of Two Types of Luteal Cells Isolated from Mature Human Corpora Lutea of Menstrual Cycle*

Abstract: Enriched small and large cell fractions were prepared from mature corpora lutea from 15 women in the midluteal phase by enzymatic dissociation, followed by Percoll gradient centrifugation. The steroidogenic function of each cell type was assessed by measuring the gonadal steroids released into the incubation medium. The large cell fraction was estimated to be 97% pure, with minimal contamination by small cells, whereas the small cell fraction was approximately 68% pure, being contaminated with 10% large cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
57
1
4

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(67 citation statements)
references
References 25 publications
5
57
1
4
Order By: Relevance
“…In the corpus luteum, luteinized granulosa cells are large polygonal cells with abundant cyto¬ plasm, while luteinized theca cells are small (about half the size of luteinized granulosa cells), with less abundant, darkly staining cytoplasm (Clement, 1987 (Channing, 1969;Lipsett, 1986); Ohara et al (1987) have demonstrated that small and large human luteal cells have steroidogenic properties similar to those exhibited by follicular thecal and granulosa cells, respectively. Our current study ofthe localization of immunoreactivity of P-450,7a and P-450AROM is consistent with this theory.…”
Section: Discussionmentioning
confidence: 98%
“…In the corpus luteum, luteinized granulosa cells are large polygonal cells with abundant cyto¬ plasm, while luteinized theca cells are small (about half the size of luteinized granulosa cells), with less abundant, darkly staining cytoplasm (Clement, 1987 (Channing, 1969;Lipsett, 1986); Ohara et al (1987) have demonstrated that small and large human luteal cells have steroidogenic properties similar to those exhibited by follicular thecal and granulosa cells, respectively. Our current study ofthe localization of immunoreactivity of P-450,7a and P-450AROM is consistent with this theory.…”
Section: Discussionmentioning
confidence: 98%
“…Density gradient centrifugation (Lahteenmaki et al, 1982; Magoffin and Erickson, 1988) or flow cytometry (Hatfield and Hymer, 1986a; 1986b) is useful for separation and purification of living cells 'Correspondence. Received 6 July 1992. and have been applied to many types of cell including granulosa cells (Hirshfield et al, 1988), luteal cells (Ohara et al, 1987) and Leydig cells (Gale et al, 1982). Separation methods such as unit gravity sedimentation or Percoli gradient have yielded large cell preparations that are usually contaminated with small cells (Koos and Hansel, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…The patients received Brc continuously at three different dose levels of 1.25, 2.5, and Ohara et al (1987). The intrassay coefficients of variation were 5.5% for LH, 6.5% for FSH, 6.8% for PRL, 5.0% for E2, 6.5% for E1, 5.7% for P, 6.7% for T, 6.2% for DHAS, 5.4% for DHA, and 6.5% for ASD, respectively.…”
Section: Methodsmentioning
confidence: 99%